Mouse models for BRAF-induced cancers. (25th October 2007) - Pritchard, C.; Carragher, L.; Aldridge, V.; Giblett, S.; Jin, H.; Foster, C.; Andreadi, C.; Kamata, T.
Abstract : Oncogenic mutations in the BRAF gene are detected in ∼7% of human cancer samples with a particularly high frequency of mutation in malignant melanomas. Over 40 different missense BRAF mutations have been found, but the vast majority (>90%) represent a single nucleotide change resulting in a valine→glutamate mutation at residue 600 ( V600E BRAF ). In cells cultured in vitro, V600E BRAF is able to stimulate endogenous MEK [MAPK (mitogen-activated protein kinase)/ERK (extracellular-signal-regulated kinase) kinase] and ERK phosphorylation leading to an increase in cell proliferation, cell survival, transformation, tumorigenicity, invasion and vascular development. Many of these hallmarks of cancer can be reversed by treatment of cells with siRNA (small interfering RNA) to BRAF or by inhibiting MEK, indicating that BRAF and MEK are attractive therapeutic targets in cancer samples with BRAF mutations. In order to fully understand the role of oncogenic BRAF in cancer development in vivo as well as to test the in vivo efficacy of anti-BRAF or anti-MEK therapies, GEMMs (genetically engineered mouse models) have been generated in which expression of oncogenic BRaf is conditionally dependent on the Cre recombinase. The delivery/activation of the Cre recombinase can be regulated in both a temporal and spatial manner and therefore these mouse models can be used to recapitulate the somatic mutation of BRAF that occurs in different tissues in the development of human cancer. The data so far obtained following Cre-mediated activation in haemopoietic tissue and the lung indicate that V600E BRAF mutation can drive tumour initiation and that its primary effect is to induce high levels of cyclin D1-mediated cell proliferation. However, hallmarks of OIS (oncogene-induced senescence) are evident that restrain further development of the tumour.